Conciencia tributaria y pago de arbitrios en los comerciantes del mercado Cardozo del Distrito de San Juan, año 2023 - De la Cruz Donayre, Julio Daniel (2024)
The objective of this research was to determine the relationship between tax awareness and the payment of excise taxes among the merchants of the Cardozo Market in the district of San Juan, year 2023. Then, the research methodology comprised a basic type, correlational and non-experimental design, in addition to a sample composed of 150 participants among merchants of the Cardozo Market of the district of San Juan and independent experts in tax matters for the purpose of applying the questionnaire, after resorting to a probabilistic sampling. The main results showed the importance of the promotion and consolidation of tax awareness (through the knowledge of tax regulations and compliance with tax obligations, within the framework of awareness talks, in order to develop values such as honesty, responsibility and integrity) and payment of taxes (based on the establishment of collection strategies such as the granting of tax benefits, tax discounts and payment facilities for all types of taxes) by the merchants of the Cardozo Market. Finally, the main conclusion was that there is a significant relationship between tax awareness and the payment of excise taxes among the merchants of the Cardozo Market in the district of San Juan, year 2023. This conclusion was supported by the Spearman Correlation index obtained for the general hypothesis, whose value was 0.896.